Cadmium concentration in seawater, sediment and soft tissues of bivalves in the harvesting area in Van Don, Quang Ninh province - Thien, Luu Ngoc; Thanh, Nguyen Cong (Vietnam Journal of Marine Science and Technology, 2019)
Cd concentrations were determined in coastal water, sediments and soft tissues of molluscs (hakf-crenate ark (Anadara subcrenata), noble scallop (Mimachlamys nobilis) and undulating venus (Paphia undulata)), which were collected from two stations in the harvesting area in Van Don, Quang Ninh province in 2014. In this study, cadmium concentration in seawater ranged from 0.22 µg.l-1 to 1 µg.l-1 while the concentration in sediment was from 0.59 mg.kg-1 to 1.55 mg.kg-1. Cd accumulated in hakf-crenate ark (Anadara subcrenata), noble scallop (Mimachlamys nobilis) and undulating venus (Paphia undulata) ranged from 0.81 mg.kg-1 to 1.48 mg.kg-1; from 0.35 mg.kg-1 to 2.23 mg.kg-1; from 0.25 mg.kg-1 to 0.81 mg.kg-1, respectively. Research result also showed that cadmium concentration in seawater in rainy season was higher than that in dry season while a contrary trend occurred in sediment. There was a weak correlation between Cd concentration in seawater and concentration of Cd in sediment in this area (r = 0.24). The cadmium fraction in sediment in this area was contributed as follows: residual component (F5) > Mn, Fe oxyhydroxide (F3) > organic matter-bound (F4) > acid soluble (F2) > ion-changeable (F1). Cadmium levels in tissues were in the order of stomach > mantle > gill > foot. Beside, cadmium components in adductor muscle of noble scallop were lowest. Therefore, the risk level for customer when consuming undulating venus (Paphia undulata), hakf-crenate ark (Anadara subcrenata) and adductor muscle was not high.